Long-Term Trend Analysis of Changing Precipitation in Tamil Nadu, India - Sivajothi, R.; Karthikeyan, K. (International Journal of Engineering and Technology, 2018)
Spatial and temporal precipitation changeability in Tamil Nadu State in India was analyzed by utilizing month to month precipitation information for a long time (1901-2002) from 29 stations. Tamil Nadu is one of the southern states of India which has a farming-based economy. Senâ€™s slope method has been used to estimate the magnitude of trend, whose statistical significance was assessed by the Mann-Kendall test, the highest decreases were observed in a summer precipitation and annual precipitation decreasing trends were detected at many stations in January, February and June. The coefficient of variation (CV) was used to analyze precipitation variability. The Slope test depicts a decreasing trend at all Stations over the past 102 years, from the results obtained by both Parametric and Non-parametric tests for annual and monsoon precipitation at 5% level of significance. The Weakening precipitation of the monsoon circulation parameters caused by global warming appears to be the main causes of recent changes. The most elevated inconstancy was seen in the monsoon precipitation and least fluctuation was seen in the late summer over the 102 years (1901-2002). The weakening precipitation of the monsoon circulation parameters caused by gradual increase in the overall temperature of the earth is the major cause of recent changes.Â